Perspectives for epidemiology within the reform to the social security (1999)
The reform to the social security systems generated new fields of action for epidemiology, particularly those related to strategies for social and sanitary justice. In the first strategy the epidemiological method can operate in the diagnosis and in the process of establishing priorities, as well as in the design of the model form intervention, preserving or improving equity. In the second, the orientation of epidemiology for the administrations of health services would prevent deviations and would suggest corrections to optimize their use, aiming at the elimination of those unjust factors that can be avoided.